2022
DOI: 10.1177/0271678x221098811
|View full text |Cite
|
Sign up to set email alerts
|

Temporal brain transcriptome analysis reveals key pathological events after germinal matrix hemorrhage in neonatal rats

Abstract: Germinal matrix hemorrhage (GMH) is a common complication in preterm infants and is associated with high risk of adverse neurodevelopmental outcomes. We used a rat GMH model and performed RNA sequencing to investigate the signaling pathways and biological processes following hemorrhage. GMH induced brain injury characterized by early hematoma and subsequent tissue loss. At 6 hours after GMH, gene expression indicated an increase in mitochondrial activity such as ATP metabolism and oxidative phosphorylation alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Further, another study reported a link between ALAS2 and ferroptosis. Specifically, Song et al found that ALAS2 expression was regulated by the ferroptosis response in a rat germinal matrix hemorrhage model, which may affect the molecular mechanisms of brain injury ( 36 ). These studies highlight the potential of ALAS2 to serve as an interventional target for a range of iron-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Further, another study reported a link between ALAS2 and ferroptosis. Specifically, Song et al found that ALAS2 expression was regulated by the ferroptosis response in a rat germinal matrix hemorrhage model, which may affect the molecular mechanisms of brain injury ( 36 ). These studies highlight the potential of ALAS2 to serve as an interventional target for a range of iron-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 ] HMOX1 is also a key target in the process of ferroptosis. [ 51 ] In the acute stage of ICH, HMOX1 catalyzes excessive heme decomposition, resulting in iron overload, which may directly lead to ferroptosis. This similar mechanism has been confirmed in acute myocardial injury caused by hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, ferroptosis and mitochondrial dysfunction were found at early time points after GMH in the PND5 GMH rat model. 27 Brain injury after GMH includes the acute physical effects of bleeding 14 and the secondary injury arising from heme and free iron-induced cytotoxicity and regulated neural cell death, which can persist for a long time and are associated with long-term neurological disabilities and thus have attracted much attention in the study of post-hemorrhagic brain injury mechanisms. It has been shown that even low-grade GMH may impair normal oligodendrogenesis thus leading to white matter injury, 41 and immune cell infiltration and inflammation have been shown to play important roles in GMH-induced secondary brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Following anesthesia with isoflurane (5% for induction and 3.5% for maintenance) in a mixture of oxygen and nitrogen, 0.3 U collagenase VII (Sigma) in 2 µl saline or saline alone was injected into the right middle medial striatum for induction of GMH as previously described. 27 Briefly, injections were administered at 1 μL/min for 2 min in the right hemisphere 1 mm rostral of the bregma and 4 mm lateral of the midline, and 3.5 mm in depth using a 28G needle and a 25 μL Hamilton syringe connected to an infusion pump (CMA/100 microinjection pump). The animals were allowed to recover on a heating pad set to 35°C before being returned to their dams.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation